Stabilizing Quadruped Robot Movement Using Fuzzy Logic Control for Yaw Angle Adjustment in Walking and Troting Gait - Izzah, Sukma Nurul; Dharmawan, Andi; Auzan, Muhammad; Sumbodo, Bakhtiar Alldino Ardi; Istiyanto, Jazi Eko (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2024)
Balance is a fundamental aspect of quadruped robots that determines their movement success. Imbalanced movement can affect the robot's orientation, leading to potential deviations from the intended direction due to changes in the attitude angle. An unstable attitude angle can result in loss of control, complicating effective navigation. This loss of control may prevent the robot from maintaining its stability, increasing the risk of falling. This study designs a control system for a quadruped robot using fuzzy control system to manage the yaw angle while the robot walks forward using both walking and trotting gaits. The fuzzy control system outputs are used to adjust the hip joint angles of the robot's four legs, modifying the stride length of each leg accordingly. The quadruped robot was tested with both walking and trotting gaits moving forward for 30 seconds. The quadruped robot successfully maintained balance and stability in the ?-axis (yaw) on a flat, obstacle-free surface using fuzzy control system. The fuzzy logic control effectively reduced positional distance fluctuations from the set point and enhanced the robot's ability to return to the set point after fluctuations, without producing excessive overshoot.